Demarcando vestígios: definindo (o território de) indígenas em isolamento voluntário na Terra Indígena Massaco - Pereira, Amanda Villa (2018)
The presence of reports in the big mass media spreading the existence of isolated indigenous people in the Amazon forest has grown exponentially over the last years. Such movement is associated mainly due to the onslaughts of a “developmental” nature that is moving forward to lands that are most wanted from the predatory capitalism, along with persistent illegal activities looking for timber and other resources from the forest. Yet, Brazil is a reference when it comes to protection measures to such indigenous communities, and this reputation is due mostly to policies related to demarcation of lands, highlighting the demarcation of an indigenous area exclusively to isolated people in 1996: the indigenous land called Massaco, in the state of Rondônia. In order to enable the land demarcation, it was necessary to create innovations regarding demarcation procedures, in which, as a matter of course, must host the attendance of the indigenous themselves when defining their traditional territory. Regarding the Massaco’s area, it was by the track and traces from an indigenous group that their territory and existence have been defined, while their image is still being designed as an ongoing study of the artifacts found, forsaken Camps, appearance reports and distance observations: they cannot be heard, obviously, therefore they cannot define “their” own territory. The aim of this research is to explore the debates related to the identification of such groups in order to, subsequently, investigate how the land demarcation took place, as well as seeking the knowledge of how their image remains continuously under negotiation at the politics scope for the isolated indigenous people from Rondônia and the Brazilian Amazon.